2019
DOI: 10.1177/0391398819893382
|View full text |Cite
|
Sign up to set email alerts
|

Regional citrate versus systemic heparin anticoagulation for continuous renal replacement therapy in critically ill children

Abstract: Objectives: Anticoagulation is used to prevent filter clotting in patients undergoing continuous renal replacement therapy. Regional citrate anticoagulation is associated with lower rates of bleeding complications and prolongs the filter life span; however, a number of metabolic side effects had been associated with this therapy. The aim of this study was to evaluate the effect and safety of citrate versus heparin anticoagulation for continuous renal replacement therapy in critically ill children. Methods: A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In line with previous experiences reported in the literature ( 36 , 37 ), we found that dimension of vascular access and anticoagulation strategy were independent predictors for circuit clotting. In particular, smaller vascular access (≤ 8 Fr) was significantly associated with filter clotting.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous experiences reported in the literature ( 36 , 37 ), we found that dimension of vascular access and anticoagulation strategy were independent predictors for circuit clotting. In particular, smaller vascular access (≤ 8 Fr) was significantly associated with filter clotting.…”
Section: Discussionsupporting
confidence: 92%
“…Ten of the eleven selected studies report CL or clotting rate as treatment outcomes [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] ( Table 3 ). Eight studies reporting CL as treatment outcomes, and cumulatively counting for 1550 procedures, consistently identify the superiority of RCA over systemic anticoagulation with heparin in prolonging CL.…”
Section: Resultsmentioning
confidence: 99%
“…The exposure of whole blood to large adsorbent surfaces in therapeutic apheresis requires adsorbent polymers of particularly high blood compatibility to avoid adverse reactions at the blood-adsorbent interface, 26 such as activation of immune cells or platelets. While device-related parameters including the chemical composition, charge, and morphology of adsorbent polymers and the choice of the anticoagulant can influence blood cell activation in the extracorporeal circuit, 18 , 27 , 28 30 host-related factors may play a role, as well.…”
Section: Discussionmentioning
confidence: 99%